Heating, cooling, lighting : sustainable design strategies towards net zero architecture - Lechner, Norbert; Andrasik, Patricia (Hoboken, NJ : John Wiley & Sons, 2022)
"Heating, Cooling, Lighting, the leading guide to environmental control systems design for over 25 years, provides future architects and practicing professionals with the knowledge and tools needed to design a sustainable built environment at the schematic design stage. This book treats heating, cooling, and lighting not as isolated topics, but as integrated parts towards manipulating the environment to achieve net zero consumption. Responding to current industry trends, this Fifth Edition has been completely restructured based on net zero design strategies. Reflecting the latest developments in codes, standards, and rating systems for energy efficiency, this Fifth Edition includes three new chapters: Retrofits - best practices for efficient energy optimization in existing buildings, Integrated Design - strategies for synergizing passive and active design, and Design Tools - how to utilize the best tools to benchmark a building's sustainability and net zero potential; as well as an extensively updated Lighting chapter. Instructor's have access to an Instructor's Manual that includes exercises, projects, discussion questions, and web resources"--
Keywords: Heating; Air conditioning; Lighting